The Potential for Innovative and Smart Rural Development in the Peripheral Regions of Eastern Poland: A Recent Study - Adamowicz, Mieczyslaw (Current Topics in Agricultural Sciences Vol. 3, 2021)
Peripheral regions exist in most European countries, and in the countries of the European Union they have been supported for many years by the Community’s Cohesion Policy, which aims at reducing development disparities between the Member States and regions within individual countries. In Poland, five out of sixteen voivodeships in the country are considered to be peripheral regions. They are located on Poland’s eastern border, which is also the eastern border of the European Union. Support programmes for these regions have attained the status of separate operational programmes, focusing on generating convergence effects, which can be achieved by increasing the level of innovation and implementing intelligent ways of operating the economy. The peripheral regions are characterised by the outflow of resources, a narrow sectoral structure and price-taking firms in a dependent relationship with external customers. The aim of this paper is to demonstrate the essence of peripherality and the innovative-development potential of peripheral regions in Poland, as well as the potential of smart rural development. The paper is based on an analysis of research results drawn from the literature on the subject, as well as from official information and statistics. Own research on the smart village concept in three regions of Eastern Poland was also used. This research showed a reduction in disproportions in the development of regions in Poland, and a link between the level of innovation and the economic growth of the regions, which occurred with a certain lag in relation to the transfer of innovation.